Synthesis of Amphiphilic Blockcopolymer Using Mechanically Produced Macromonomers Possessing Anhydrate as a Terminal Group and Its Application to Polymeric Micelles - Shin-ichi Kondo; Machi Omoto; Yuka Sawama; Yasushi Sasai; Kenjiro Tatematsu; Yukinori Yamauchi; Masayuki Kuzuya (Journal of Pharmacy and Nutrition Sciences, 2014)
We have synthesized macromonomers by mechanochemical reaction of poly(benzyl methacrylate) (PBzMA) and maleic anhydride (MA). The ESR spectrum of the fractured sample of PBzMA and MA showed a broad singlet, which was apparently different from the spectrum of PBzMA mechanoradical. The amphiphilic blockcopolymer was synthesized with macromonomer of PBzMA and amino-terminated polyethyleneglycol (a-methyl-w-aminopropoxy polyoxyethylene, MEPA). The number average molecular weight of the produced amphiphilic blockcopolymer was 33,000. Polymeric micelles were readily prepared from the present amphiphilic blockcopolymer by a dialysis method. The mean diameter of the micelles measured by dynamic light scattering was about 146 nm. It was shown that the present macromonomer mechanically produced can be used for the synthesis of amphiphilic bockcopolymer to form polymeric micelles.